2010
DOI: 10.4103/0974-2948.71054
|View full text |Cite
|
Sign up to set email alerts
|

Palatal rugoscopy: Establishing identity

Abstract: Palatal rugae are irregular, asymmetric ridges of the mucous membrane extending laterally from the incisive papilla and the anterior part of the palatal raphe. The uniqueness and the overall stability of palatal rugae suggest their use for forensic identification.Objective:The purpose of this study was to compare the palatal rugae patterns in 2 different populations in India (Madhya Pradesh and Kerala), and furthermore, to assess the predominant pattern if any in the selected groups.Materials and Methods:60 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
4
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 6 publications
8
57
4
6
Order By: Relevance
“…This finding indicates the need for describing/identifying other shapes and conducting a larger scale study. The findings of this study confirm previous findings with respect to Egyptian and Saudi children [1], Saudi adults [9], and Indians [13,21,26] where wavy and curved rugae are the most common shapes followed by straight rugae. The results are also consistent with those reported for Australian Aborigines and Caucasian populations as they, too, are found to have a higher prevalence of wavy-and curved-shaped rugae [14].…”
Section: Discussionsupporting
confidence: 82%
“…This finding indicates the need for describing/identifying other shapes and conducting a larger scale study. The findings of this study confirm previous findings with respect to Egyptian and Saudi children [1], Saudi adults [9], and Indians [13,21,26] where wavy and curved rugae are the most common shapes followed by straight rugae. The results are also consistent with those reported for Australian Aborigines and Caucasian populations as they, too, are found to have a higher prevalence of wavy-and curved-shaped rugae [14].…”
Section: Discussionsupporting
confidence: 82%
“…In this study, the mean straight pattern was more among males and mean circular pattern was the least among females. These results are in contrary to the study conducted by Paliwal et al 8 and Kallianpur et al, 9 who said that the predominant shape was wavy. Intergroup comparisons of rugae shape revealed that the curved type was more among males and the wavy type higher in females, which was statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
“…Paliwal et al, in 2010 determined the number and pattern of palatal rugae among Madhya Pradesh and Kerala populations of India and reported that straight rugae pattern on the right side of the palate among males were significantly predominant when compared to Madhya Pradesh population [33]. Kashima et al, compared the palatine rugae and shape of the hard palate among Japanese and Indians children and reported that Japanese children had more primary rugae than Indian children and the palatal raphe of Japanese children were wider than those of the Indian children [34].…”
Section: Resultsmentioning
confidence: 99%